Impact of Increasing Levels of Oxygen Consumption on the Evolution of Color, Phenolic, and Volatile Compounds of Nebbiolo Wines - Petrozziello, Maurizio; Torchio, Fabrizio; Piano, Federico; Giacosa, Simone; Ugliano, Maurizio; Bosso, Antonella; Rolle, Luca (Frontiers in Chemistry, 2018)
Since the end of the last century, many works have been carried out to verify the effect of controlled oxygen intake on the chemical and organoleptic characteristics of red wines. In spite of the large number of studies on this subject, oxygen remains a cutting-edge research topic in oenology. Oxygen consumption leads to complex and not univocal changes in wine composition, sometimes positive such as color stabilization, softening of mouthfeel, increase of aroma complexity. However, the variability of these effects, which depend both on the oxygenation conditions and the composition of the wine, require more efforts in this research field to effectively manage wine oxygen exposure. The present study is focused on the evolution of the chemical composition of four different Nebbiolo wines, each of them added with 4 different doses of oxygen (7, 14, 21, and 28 mg/L total intake) during the first month of storage. In this perspective, the evolution over time of wine color and polyphenols was studied. Acetaldehyde, glyceraldehyde and glyoxylic acid were quantified by HPLC. These compounds can play a role in wine aging creating condensed colored and stable products involving anthocyanins with or without tannins. Moreover, some volatile aldehydes correlated with oxidized olfactory notes, including methional and (E)-2-alkenals, have been quantified by GC-MS. Overall, during storage a decrease of color intensity, total and free anthocyanins and an increase in polymeric pigments (in particular the contribution to the red color of pigments not-bleachable by SO2 or dTAT%) and some minor aldehydes was observed. Nevertheless, the differences in color parameters between the samples with different doses of oxygen were modest. These evidences were in contrast with an evident and detectable increase of free acetaldehyde content at increasing doses of oxygen measured after 60 days of storage. The effect of oxygen on color and production of SO2 non-bleachable pigments during ageing varies with wine composition, with Nebbiolo wines appearing not very reactive in this respect, probably due to their low content in anthocyanins and high content in tannins.